Solubilization of ibuprofen for freeze dried parenteral dosage forms - Preskar Maja; Vrbanec Tomislav; Vrečer Franc; Šket Primož; Plavec Janez; Gašperlin Mirjana (Acta Pharmaceutica)
Ibuprofen, a weakly acidic non-steroidal anti-inflammatory drug having poor aqueous solubility, is a challenging drug for the development of pharmaceutical formulations, resulting in numerous research attempts focusing on improvement of its solubility and consequently bioavailability. Most studies have been done for solid dosage forms, with very little attention paid to parenterals. Hence, the main purpose of the present study was to enhance ibuprofen solubility as a result of formulation composition and the freeze drying process. Moreover, the purpose was to prepare a freeze dried dosage form with improved ibuprofen solubility that could, after simple reconstitution with water for injection, result in an isotonic parenteral solution. Solubility of ibuprofen was modified by various excipients suitable for parenteral application. Drug interactions with selected excipients in the final product/lyophilisate were studied by a combined use of XRPD, DSC, Raman and ss-NMR. Analyses of lyophilized samples showed solubility enhancement of ibuprofen and in situ formation of an ibuprofen salt with the alkaline excipients used.